Analytical models for the perforation of thick and thin thickness woven-laminates subjected to high-velocity impact. (15th June 2018) - Alonso, Luis; Navarro, Carlos; García-Castillo, Shirley K.
Abstract: This paper deals with the problem of high-velocity impact of a low-mass projectile on woven composite plates. A nondimensional formulation of two analytical models has been developed (one for thin laminates and the other for thick ones). Both analytical models are based on energy conservation and have been applied for the ballistic impact on E-glass woven fibres/polyester composite plates. The results of the models (mainly the ballistic limits) have been compared with experimental results. The value of the ratio target thickness/projectile diameter determining whether the laminate behaves as thick or thin has been established.